Stubborn Structures : Reconceptualizing Post-Communist Regimes - Magyar, Bálint, 1952- (Book collections on Project MUSE., 2019)
The present volume represents a major step forward in the effort to understand post-communist politics in ways that escape the procrustean bed of theory oriented primarily to the democratization research agenda.